Language dominance assessment in a bilingual population: Validity of fMRI in the second language. Issue 10 (2nd September 2014) - Centeno, Maria; Koepp, Matthias J.; Vollmar, Christian; Stretton, Jason; Sidhu, Meneka; Michallef, Caroline; Symms, Mark R.; Thompson, Pamela J.; Duncan, John S.
Summary Objective Assessment of language dominance using functional magnetic resonance imaging (fMRI) is a standard tool to estimate the risk of language function decline after epilepsy surgery. Although there has been considerable research in the characterization of language networks in bilingual individuals; little is known about the clinical usefulness of language mapping in a secondary language in patients with epilepsy, and how language lateralization assessed by fMRI may differ by the use of native or a secondary language paradigms. In this study we investigate language representation in a population of nonnative English speakers to assess differences in fMRI language lateralization between the first (native) and second language (English). Methods Sixteen nonnative English‐speaking patients with focal drug‐resistant epilepsy underwent language fMRI in their first (native) language (L1) and in English (L2). Differences between language maps using L1 and L2 paradigms were examined at the single subject level by comparing within‐subject lateralization indexes obtained for each language. Differences at the group level were examined for each of the tasks and languages. Results Group maps for the second language (English) showed overlapping areas of activation with the native language, but with larger clusters, and more bilaterally distributed than for the first language. However, at the individual level, lateralization indexes were concordant between the two languages, except for one patient with bilateral hippocampal sclerosis who was left dominant in English and showed bilateral dominance for verb generation and right dominance for verbal fluency in his native tongue. Significance Language lateralization can generally be reliably derived from fMRI tasks in a second language provided that the subject can follow the task. Subjects with greater likelihood of atypical language representation should be evaluated more carefully, using more than one language paradigm.